Y eso, ¿con qué se come? Folclore culinario e identidad en Kazajistán rural contemporáneo - Jiménez Tovar, Soledad (El Colegio de México, 2015)
This article studies food folklore and identity in contemporary rural Kazakhstan, particularly the Dungan narodnost, which is a Chinese-speaking Muslim community historically perceived as an example of cultural conservation. This work aims to provide an overview, from the Dungan perspective, of the features that determine the cultural differentiation and ethnic classification within the region. Based on fifteen months of fieldwork carried out between 2011 and 2013 in Southern Kazakhstan, the work analyzes the Dungan’s material culture, specifically their food and utensils. The article is further divided into four sections: a general description of Central Asia’s Dungans, a pair of ethnographic vignettes, the vignette’s context, and, lastly, ways in which cultural conservation and folklore can be studied from a new perspective within the Central Asian context.